Decorating with plants : what to choose, ways to style, and how to make them thrive - Chapman, Baylor (Artisan, 2019)
Houseplants are more popular than ever before<U+2014>especially with millennials, who are setting up their homes for the first time and discovering that nothing can add energy, style, and that essential “lived-in-ness” to their spaces better than a little bit of green. Whether it<U+2019>s a statement-making fiddle-leaf fig or a tiny tabletop succulent, a houseplant instantly elevates the look of your home. But where to begin? In Decorating with Plants, Baylor Chapman walks readers through everything they need to know to bring houseplants into their home. First, there<U+2019>s Plant Care 101: from how to assess light conditions to tricks for keeping your plants alive while on vacation, Chapman gives readers the simple, foundational info they need to ensure their plants will thrive. Then she introduces us to 28 of her favorites<U+2014>specimens that are tough as nails but oh-so-stylish, from the eye-catching Rubber Tree to the delicate Cape Primrose. Finally, she guides readers through the home room by room: Place an aromatic plant like jasmine or gardenia to your entry to establish your home<U+2019>s “signature scent.” Add a proper sense of scale to your living room with a ceiling-grazing palm. Create a living centerpiece of jewel-toned succulents for a dining table arrangement that will last long after your dinner party. From air purification to pest control, there<U+2019>s no limit to what houseplants can do for your home<U+2014>and Decorating with Plants is here to show you how to add them to spaces big and small with style.